PENGARUH GAYA KEPEMIMPINAN, KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT WITAPONDA KABUPATEN MOROWALI - Tobigo, Haeruddin (Katalogis, 2016)
The objectives of this research are: (1) to investigate and analiyze the effect of leadership style, job satisfaction and organizational commitment simultaneously on personnel performance at Witaponda Subdistrict Head Office, Morowali Regency, (2) to investigate and analyze the effect of leadership style on personnel performance, (3) to investigate and analyze the effect job satisfaction on personnel performance, (4) to investigate and analyze the effect of organizational commitment on personnel performance. This is a descriptive causal research to investigate the interrelationship among variables involving 33 samples which have been determined using census method. Base on the result of multiple linear regression, it is found that : (1) leadership style, job satisfaction and organizational commitment simultaneously perform positive and significant effect on personnel performance at Witaponda Subdistrict Head Office, Morowali Regency, (2) leadership style performs positive and significant effect on personnel performance, (3) job satisfaction perform positive and significant effect on personnel performance, (4) organizational commitment perform positive and significant effect on personnel performance.